Physical mechanisms and models of the long-term transformations in radiative recombination observed in n-GaAs under microwave irradiation - Milenin, G.V.; Red’ko, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Simulation of long-term changes in photoluminescence of n-GaAs after microwave treatment by using the analysis of random events underlying the processes of evolution of the defect structure has been performed. We have shown the agreement of the experimental and theoretical time dependences of the changes in the photoluminescence intensity provided that the distribution of the random variable – time to a random event – obeys the Weibull–Gnedenko law. The mechanisms of transformation of the defect structure, which are based on the dynamics of behavior of dislocations and impurity complexes owing to microwave irradiation, have been presented.